A gene signature derived from the loss of cdkn1a (P21) is associated with CMS4 colorectal cancer - Bueno-Fortes, Santiago; Muenzner, Julienne K.; Berral-Gonzalez, Alberto; Hampel, Chuanpit; Lindner, Pablo; Berninger, Alexandra; Hübner, Kerstin; Kunze, Philipp; Bäuerle, Tobias; Erlenbach-Wünsch, Katharina; Sánchez-Santos, José Manuel; Hartmann, Arndt; et al. (Cancers, 2022)
The epithelial–mesenchymal transition (EMT) is associated with tumor aggressiveness and increased invasion, migration, metastasis, angiogenesis, and drug resistance. Although the HCT116 p21-/- cell line is well known for its EMT-associated phenotype, with high Vimentin and low E-cadherin protein levels, the gene signature of this rather intermediate EMT-like cell line has not been determined so far. In this work, we present a robust molecular and bioinformatics analysis, to reveal the associated gene expression profile and its correlation with different types of colorectal cancer tumors. We compared the quantitative signature obtained with the NanoString platform with the expression profiles of colorectal cancer (CRC) Consensus Molecular Subtypes (CMS) as identified, and validated the results in a large independent cohort of human tumor samples. The expression signature derived from the p21-/- cells showed consistent and reliable numbers of upregulated and downregulated genes, as evaluated with two machine learning methods against the four CRC subtypes (i.e., CMS1, 2, 3, and 4). High concordance was found between the upregulated gene signature of HCT116 p21-/- cells and the signature of the CMS4 mesenchymal subtype. At the same time, the upregulated gene signature of the native HCT116 cells was similar to that of CMS1. Using a multivariate Cox regression model to analyze the survival data in the CRC tumor cohort, we selected genes that have a predictive risk power (with a significant gene risk incidence score). A set of genes of the mesenchymal signature was proven to be significantly associated with poor survival, specifically in the CMS4 CRC human cohort. We suggest that the gene signature of HCT116 p21-/- cells could be a suitable metric for mechanistic studies regarding the CMS4 signature and its functional consequences in CRC. Moreover, this model could help to discover the molecular mechanisms of intermediate EMT, which is known to be associated with extraordinarily high stemness and drug resistance.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CAM model; CDKN1A; Colorectal cancer; Consensus molecular subtypes (CMS); Epithelial–mesenchymal transition (EMT); HCT116 cells; Intermediate EMT; SNAI2

A partial epithelial-mesenchymal transition signature for highly aggressive colorectal cancer cells that survive under nutrient restriction - Pastorino, Gil; Sheraj, Ilir; Hübner, Kerstin; Ferrero, Giulio; Kunze, Philipp; Hartmann, Arndt; Hampel, Chuanpit; Husnugil, Hepsen Hazal; Maiuthed, Arnatchai; Gebhart, Florian; Schlattmann, Fynn; Gulec Taskiran, Aliye Ezgi; et al. (Journal of Pathology, 2024)
Partial epithelial-mesenchymal transition (p-EMT) has recently been identified as a hybrid state consisting of cells with both epithelial and mesenchymal characteristics and is associated with the migration, metastasis, and chemoresistance of cancer cells. Here, we describe the induction of p-EMT in starved colorectal cancer (CRC) cells and identify a p-EMT gene signature that can predict prognosis. Functional characterisation of starvation-induced p-EMT in HCT116, DLD1, and HT29 cells showed changes in proliferation, morphology, and drug sensitivity, supported by in vivo studies using the chorioallantoic membrane model. An EMT-specific quantitative polymerase chain reaction (qPCR) array was used to screen for deregulated genes, leading to the establishment of an in silico gene signature that was correlated with poor disease-free survival in CRC patients along with the CRC consensus molecular subtype CMS4. Among the significantly deregulated p-EMT genes, a triple-gene signature consisting of SERPINE1, SOX10, and epidermal growth factor receptor (EGFR) was identified. Starvation-induced p-EMT was characterised by increased migratory potential and chemoresistance, as well as E-cadherin processing and internalisation. Both gene signature and E-cadherin alterations could be reversed by the proteasomal inhibitor MG132. Spatially resolving EGFR expression with high-resolution immunofluorescence imaging identified a proliferation stop in starved CRC cells caused by EGFR internalisation. In conclusion, we have gained insight into a previously undiscovered EMT mechanism that may become relevant when tumour cells are under nutrient stress, as seen in early stages of metastasis. Targeting this process of tumour cell dissemination might help to prevent EMT and overcome drug resistance. © 2024 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2024-01-26
Keywords: consensus molecular subtype 4; E-cadherin processing; EGFR internalisation; intermediate EMT; partial EMT; prognosis; proteasome; starvation

ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

DAPK1 loss triggers tumor invasion in colorectal tumor cells - Steinmann, Sara; Kunze, Philipp; Hampel, Chuanpit; Eckstein, Markus; Bertram Bramsen, Jesper; Muenzner, Julienne K.; Carlé, Birgitta-Elisabeth; Ndreshkjana, Benardina; Kemenes, Stephan; Gasparini, Pierluigi; Friedrich, Oliver; Andersen, Claus; et al. (Cell Death & Disease, 2019)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death worldwide. Despite the improvement of surgical and chemotherapeutic treatments, as of yet, the disease has not been overcome due to metastasis to distant organs. Hence, it is of great relevance to understand the mechanisms responsible for metastasis initiation and progression and to identify novel metastatic markers for a higher chance of preventing the metastatic disease. The Death-associated protein kinase 1 (DAPK1), recently, has been shown to be a potential candidate for regulating metastasis in CRC. Hence, the aim of the study was to investigate the impact of DAPK1 protein on CRC aggressiveness. Using CRISPR/Cas9 technology, we generated DAPK1-deficient HCT116 monoclonal cell lines and characterized their knockout phenotype in vitro and in vivo. We show that loss of DAPK1 implemented changes in growth pattern and enhanced tumor budding in vivo in the chorioallantoic membrane (CAM) model. Further, we observed more tumor cell dissemination into chicken embryo organs and increased invasion capacity using rat brain 3D in vitro model. The novel identified DAPK1-loss gene expression signature showed a stroma typical pattern and was associated with a gained ability for remodeling the extracellular matrix. Finally, we suggest the DAPK1-ERK1 signaling axis being involved in metastatic progression of CRC. Our results highlight DAPK1 as an anti-metastatic player in CRC and suggest DAPK1 as a potential predictive biomarker for this cancer type.
CRIS-Team Scopus Importer:2019-12-10

Generation and characterization of hepatocellular carcinoma cell lines with enhanced cancer stem cell potential - Muenzner, Julienne K.; Kunze, Philipp; Lindner, Pablo; Polaschek, Sandra; Menke, Kira; Eckstein, Markus; Geppert, Carol-Immanuel; Chanvorachote, Pithi; Bäuerle, Tobias; Hartmann, Arndt; Schneider-Stock, Regine (Journal of Cellular and Molecular Medicine, 2018)
Hepatocellular carcinoma (HCC) is one of the most common causes for cancer-related death worldwide with rapidly increasing incidence and mortality rates. As for other types of cancers, also in HCC cancer stem cells (CSCs) are thought to be responsible for tumour initiation, progression and therapy failure. However, as rare subpopulations of tumour tissue, CSCs are difficult to isolate, thus making the development of suitable and reliable model systems necessary. In our study, we generated HepG2 subclones with enriched CSC potential by application of the spheroid formation method and subsequent single-cell cloning. Analyses in several 2D and 3D cell culture systems as well as a panel of functional assays both in vitro and in vivo revealed that the generated subclones displayed characteristic and sustained features of tumour initiating cells as well as highly aggressive properties related to tumour progression and metastasis. These characteristics could clearly be correlated with the expression of CSC markers that might have prognostic value in the clinical HCC setting. Therefore, we conclude that our CSC enriched HepG2 clones certainly represent suitable model systems to study the role of CSCs during HCC initiation, progression and drug resistance.
EVALuna2:34899

Multiphoton Microscopy Reveals DAPK1‐Dependent Extracellular Matrix Remodeling in a Chorioallantoic Membrane (CAM) Model - Kunze, Philipp; Kreiß, Lucas; Novosadová, Vendula; Roehe, Adriana V.; Steinmann, Sara; Prochazka, Jan; Geppert, Carol-Immanuel; Hartmann, Arndt; Schürmann, Sebastian; Friedrich, Oliver; Schneider-Stock, Regine (Cancers, 2022)
Cancer cells facilitate tumor growth by creating favorable tumor micro‐environments (TME), altering homeostasis and immune response in the extracellular matrix (ECM) of surrounding tissue. A potential factor that contributes to TME generation and ECM remodeling is the cytoskeleton‐associated human death‐associated protein kinase 1 (DAPK1). Increased tumor cell motility and de‐adhesion (thus, promoting metastasis), as well as upregulated plasminogen-signaling, are shown when functionally analyzing the DAPK1 ko‐related proteome. However, the systematic investigation of how tumor cells actively modulate the ECM at the tissue level is experimentally challenging since animal models do not allow direct experimental access while artificial in vitro scaffolds cannot simulate the entire complexity of tissue systems. Here, we used the chorioallantoic membrane (CAM) assay as a natural, collagen‐rich tissue model in combination with all‐optical experimental access by multiphoton microscopy (MPM) to study the ECM remodeling potential of colorectal tumor cells with and without DAPK1 in situ and even in vivo. This approach demonstrates the suitability of the CAM assay in combination with multiphoton microscopy for studying collagen remodeling during tumor growth. Our results indicate the high ECM remodeling potential of DAPK1 ko tumor cells at the tissue level and support our findings from proteomics.
CRIS-Team Scopus Importer:2022-05-20
Keywords: collagen; colon cancer; ECM remodeling; MPM; uPAR

Strong expression of EZH2 and H3K27me3 is associated with poor survival time in small cell lung cancer - Fernandes, Ana Paula; Alves, Rita Decassia S.; Watte, Guilherme; Kunze, Philipp; Roehe, Adriana Vial; Schneider-Stock, Regine (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

The Chorioallantoic Membrane Xenograft Assay as a Reliable Model for Investigating the Biology of Breast Cancer - Ranjan, Raphela A.; Muenzner, Julienne K.; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Walther, Wolfgang; Eckstein, Markus; et al. (Cancers, 2023)
The chorioallantoic membrane (CAM) assay is an alternative in vivo model that allows for minimally invasive research of cancer biology. Using the CAM assay, we investigated phenotypical and functional characteristics (tumor grade, mitosis rate, tumor budding, hormone receptor (HR) and HER2 status, Ki-67 proliferation index) of two breast cancer cell lines, MCF-7 and MDA-MB-231, which resemble the HR+ (luminal) and triple-negative breast cancer (TNBC) subgroups, respectively. Moreover, the CAM results were directly compared with murine MCF-7- and MDA-MB-231-derived xenografts and human patient TNBC tissue. Known phenotypical and biological features of the aggressive triple-negative breast cancer cell line (MDA-MB-231) were confirmed in the CAM assay, and mouse xenografts. Furthermore, the histomorphological and immunohistochemical variables assessed in the CAM model were similar to those in human patient tumor tissue. Given the confirmation of the classical biological and growth properties of breast cancer cell lines in the CAM model, we suggest this in vivo model to be a reliable alternative test system for breast cancer research to reduce murine animal experiments.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3R; alternative in vivo model; CAM model; hormone receptor; HTB-26; MCF-7; MDA-MB-231; mouse xenograft; tumor aggressiveness

Tumor budding: A predictor for metastasis in the CAM xenograft model - Muenzner, Julienne K.; Ranjan, Raphela A.; Eckstein, Markus; Erber, Ramona; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Schneider-Stock, Regine (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22